2022
DOI: 10.1108/ijopm-05-2021-0331
|View full text |Cite
|
Sign up to set email alerts
|

Does organizational readiness matter in lean thinking practices? An agency perspective

Abstract: PurposeExtant research documents the importance of lean thinking for organizations, however, as prior research has largely focused on hard lean practices, but little is known about the effects or the significance of soft lean practices. This research attempts to address this issue by examining how soft lean practices enhance organizational lean readiness, and in turn increase the success of lean implementation.Design/methodology/approachThis research adopts a single case study design in a small-medium enterpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 139 publications
0
6
0
Order By: Relevance
“…In the long term, operational performance is influenced by employee behavior, work environment, and the type of job [80]. An empirical study involving soft lean practices confirmed that they enhance organizational lean readiness for successful L4.0 in I4.0 [26]. I4.0 readiness may vary from sector to sector among the operational, managerial, and technological domains.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the long term, operational performance is influenced by employee behavior, work environment, and the type of job [80]. An empirical study involving soft lean practices confirmed that they enhance organizational lean readiness for successful L4.0 in I4.0 [26]. I4.0 readiness may vary from sector to sector among the operational, managerial, and technological domains.…”
Section: Discussionmentioning
confidence: 93%
“…An empirical study of lean practices in SMEs dealing with livestock feed manufacturing organizations concluded that lean soft practices influence organizational readiness in I4.0 [26]. A study was conducted that illustrated how SMEs can benefit from information technology (IT) usage for L4.0 to sustain competitiveness in I4.0 [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the higher level of societal norms that influence culture, aggregated traits such as higher degrees of individualism, uncertainty avoidance and power distances are found to positively affect the adoption of lean practices adoption (Pakdil and Leonard, 2017). While the impacts of the broadly categorized traits of national culture do matter, our focus, in the present research, is on cultural traits at the organizational level that serve as the context for the implementation of lean practices (Akmal et al. , 2022).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…To analyse the relationships between lean, DCs microfoundations and process innovation, we differentiate between lean operations and lean supply chain practices (Azadegan et al, 2013;Furlan et al, 2011;Hofer et al, 2012;Shah and Ward, 2007). In addition, we include the role of learning-and innovation-oriented lean cultures following previous research (Akmal et al, 2022;Bortolotti et al, 2015;Hardcopf et al, 2021;Onofrei et al, 2019;Yu et al, 2020). We hypothesize that process innovation is supported by lean practices implementation through DCs microfoundationssensing, seizing and transformingand strengthened by the presence of organizational learning-and innovation-oriented lean cultures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation